Rola kultury w życiu człowieka i narodów w nauczaniu Jana Pawła II = The role of culture in the life of the man and the nation in the teaching of John Paul II - Giemza, Bogdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
John Paul II`s speeches given during his pilgrimages to Poland, with special regard to those addressed to representatives of the world of science and culture, are the sources used to elaborate the present topic. The attention is first paid to the importance of the Papal pilgrimages to different countries of the world, with a special focus on the socio-cultural, ecclesiastical, religious and political context of these pilgrimages to his Homeland.
Keywords: Jan Paweł II, papież (1929-2005); kultura; człowiek; naród